A real-world experience of transition to robotic-assisted thoracic surgery (RATS) for lung resections - Alessandro Palleschi; Giovanni Mattioni; Giovanni Mattioni; Paolo Mendogni; Davide Tosi (Frontiers in Surgery, 2023)
ObjectiveWe report our experience of transition to robotic-assisted thoracic surgery (RATS) for lung resections with the da Vinci Xi surgical system, exposing short-term results.Materials and methodsThis is a single-center, retrospective analysis of RATS lung resections performed between April 2021 and September 2022 during our new robotic program. The surgical approach evolved over time, starting from a four-arm approach with four incisions. Alternative RATS approaches were subsequently evaluated, such as uniportal and biportal.ResultsDuring a 17-month period, 29 lung resections were performed. Of them, 16 were lobectomies, 7 were segmentectomies, and 6 were wedge resections. The most common indication for anatomical lung resection was non-small cell lung cancer. A uniportal approach was used for two simple segmentectomies and a biportal RATS was performed in five lobectomies and two segmentectomies. A mean number of 8.1 lymph nodes and a mean of 2.6 N2 and 1.9 N1 stations were resected during surgery, and no nodal upstaging was observed. Negative resection margins were 100%. There were two (7%) conversions, one to open surgery and one to video-assisted thoracic surgery (VATS). Eight (28%) patients experienced complications with no 30-day mortality.DiscussionHigh-ergonomic and high-quality views were immediately observed. After some procedures, we abandoned uniportal RATS because of the possibility of arm collisions and the necessity of a VATS-skilled surgeon at the operating table.ConclusionRATS for lung resections was safe and effective, and from the surgeon's standpoint, several practical advantages over VATS were observed. Further analysis on outcomes will help better understand the value of this technology.